Perspectives on Fracture Liaison Service in Austria: clinical and economic considerations - Kocijan, Roland; Haschka, Judith; Kraus, Daniel Arian; Pfender, Aaron; Frank, Stefan; Zwerina, Jochen; Behanova, Martina (Frontiers in Endocrinology, 2024)
Osteoporosis is a widespread disease and affects over 500,000 people in Austria. Fragility fractures are associated with it and represent an individual problem for the pa?ents, but also an enormous burden for the health care system. While trauma surgery care is well provided in Vienna, there is an enormous treatment gap in secondary preven?on aNer osteoporo?c fracture. Systema?c approaches such as the Fracture Liaison Service (FLS) aim to iden?fy osteoporosis pa?ents aNer fracture, to clarify diagnos?cally, to ini?ate specific therapy and to check therapy adherence. The aim of this ar?cle is to describe the prac?cal implementa?on and opera?onal flow of an already established FLS in Vienna. This includes the iden?fica?on of poten?al FLS inpa?ents, the diagnos?c work up and recommenda?ons for an IT-solu?on for baseline assessment and follow-up of FLS-pa?ents. We summarize the concept, benefits and limita?ons of FLS and provide prospec?ve as well as clinical and economic considera?ons for a city-wide FLS, managed from a central loca?on. Future concepts of FLS should include ar?ficial intelligence for vertebral fracture detec?on and simple IT-tools for the implementa?on of FLS in the outpa?ent sector.